2021
DOI: 10.1177/00131245211001908
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Environment, Teacher, and Girl Students’ Learning Skills

Abstract: The current research examined the effects of teachers and classrooms environment on girls’ learning skills in girls’ high schools. The main objective of the study was to analyze the classroom as a key academic and learning site in which the nature of interaction between teachers and students and among peers have a strong impact on students’ learning skills. The study covers 271 girl students from four high schools (two government and two private schools) from district Gujrat, Pakistan. A proportionate random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…Hence, it is confirmed that Satisfaction with discipline has an indirect effect on student performance through the meditation of supervision of academic activity. The study findings are aligned with the study findings of the previous studies conducted by several scholars in the field of social work education Shoaib & Ullah, 2019, 2021a, 2021b. Likewise, the study findings commission that the focus of the social work discipline is on learning skills and becoming competent in the field (Eltaiba & Ndoye, 2018).…”
Section: Resultssupporting
confidence: 86%
“…Hence, it is confirmed that Satisfaction with discipline has an indirect effect on student performance through the meditation of supervision of academic activity. The study findings are aligned with the study findings of the previous studies conducted by several scholars in the field of social work education Shoaib & Ullah, 2019, 2021a, 2021b. Likewise, the study findings commission that the focus of the social work discipline is on learning skills and becoming competent in the field (Eltaiba & Ndoye, 2018).…”
Section: Resultssupporting
confidence: 86%
“…For the last few decades, digitalized library services in developed and developing countries have been utilised. The digital transformation of libraries has not been a concern of HEIs in developed world, as developed countries have already transfigured knowledge and data by creating different online databases by means of modern technology [ 5 , 6 , 34 – 37 ]. Similarly, online libraries are also established.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Social work techniques are normally used to know the welfare of human beings across the world (Boddie, Jiao, Webster, Zhao, & Hodge, 2021;Kesen et al, 2021). However, research is conducted in different settings starting from the individual level to the large-scale studies employing different tools and techniques of qualitative and quantitative research (Anwar, Shoaib, & Javed, 2013;Mariam, Anwar, Shoaib, & Rasool, 2021;Shoaib, Latif, & Usmani, 2013;Shoaib, Munir, Masood, Ali, & Sher, 2012;Shoaib & Ullah, 2021a, 2021bUllah & Shoaib, 2021). Similarly, the social work implications are used to evaluate the welfare status of the individuals and groups (Iovu & Lazăr, 2021;Jessen & Tietjen, 2021;Kesen et al, 2021;Lei et al, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Social work is one of the academic disciplines that have practical implications in society (Beer, Phillips, & Quinn, 2021;Karagkounis, 2021;Kesen, Başer, Daşbaş, & Dziegielewski, 2021;Ullah & Shoaib, 2021). It is one of the practice-based professions that is concerned with different units of society (Mahajne, Alhuzail, & Bar-on, 2021;Shoaib & Ullah, 2021a;Steen, Straussner, & Senreich, 2021;Wilkerson, Wolfe-Taylor, & Kinney, 2021). These units include individuals, families, groups, communities, institutions, and hence the society.…”
Section: Introductionmentioning
confidence: 99%